'Socialised care futility' in the care of older people in hospital who call out repetitively: An ethnographic study. (July 2020) - Beaver, J.; Goldberg, S.E.; Edgley, A.; Harwood, R.H.
Abstract: Background: People living with dementia may call out repetitively, sometimes called disruptive vocalisation, or verbal agitation. In literature and policy, patients who call out repetitively are assumed to be expressing an unmet need, which should be met. Yet there has been little systematic study of this patient group in an acute hospital setting. Objectives: To better understand patients who call out repetitively and to identify what care looks like in an acute hospital setting. Design: Ethnography. Settings: Ten acute geriatric medical wards in two hospitals. Participants: 30 cognitively impaired patients who were calling out repetitively, and 15 members of hospital staff. Methods: Semi-structured interviews with hospital staff, 150 h of ward observations and informal conversations with staff, scrutiny of medical and nursing documentation, and measures of patient health status. Results: Patients who called out were moderately or severely cognitively impaired, often had delirium, were very physically disabled, and many were approaching the end of life. Most hospital staff were found to hold contradictory views: that calling out represents distress or unmet need, but that nothing can be done to alleviate the calling out. During informal conversations, most staff also tended to say that they intuitively recognised when intervening was likely to alleviate calling out. During observations, many staff appeared to and spoke of the ability to 'block' calling out. As a result we argue that social, emotional and physical needs may get overlooked. We argue that some calling out is due to a need that is unmeetable. We also found that while staff would talk about strategies for identifying need, observations and hospital documentation did not support evidence of systematic attempts to identify potential need. Conclusion: Calling out repetitively within a hospital setting is difficult for staff to understand and to respond to. This is because many of these patients are severely cognitively impaired, often immobile and dependent on their professional carers. We argue that a form of socialised care futility is communicated between staff and is used to rationalise becoming unresponsive to calling-out. We explain this phenomenon as resulting from two protective mechanisms: defence of staff's professional identity as competent practitioners; and defence of staff as having personal morality. Socialised care futility risks good quality care, therefore systematic strategies to assess and manage possible need should be developed, even if calling out remains irresolvable in some cases.